Infrasturactural Development in Organisation of Islamic Cooperation (OIC) Member Countries: Sukuk Mode Financing as an Alternative - Ogunbado, A.F. (Universiti Sains Islam Malaysia, 2024)
Infrastructure contributes to economic development by increasing productivity and providing amenities which enhance the quality of life and the growth of an economy. Likewise, its absence is a setback to the growth of any meaningful society’s economy. Inadequate infrastructure remains a critical issue in most countries that are members of the cooperation known as Organization of Islamic Cooperation (OIC). Sukuk as a general term is an Islamic or Shari’ah mode of financing. Having said that, the objective of this paper is to introduce Sukuk as an alternative or better option to the conventional mode of financing infrastructure as a machinery for economic and social growth of OICs countries. It is hoped that the outcomes of the study will be a great benefit to the policy makers of OICs member countries. It is also anticipated that the findings of the paper will serve as an alternative to the conventional mode of providing infrastructure in OICs countries. This paper is a library oriented paper, that is to say, it uses qualitative type of methodology in executing its objective. The finding shows that Sukuk is a better option and reliable in financing mega projects for development of Muslim nations.